Whole unfermented African locust bean (WUALBF) flour (Parkia biglobosa) as non conventional extender in frankfurter-type sausage (2016)
Frankfurter-type sausages were produced using Whole Unfermented African Locust Bean Flour (WUA LBF) to substitute Ground Beef (GB) in the product formulation at 0%, 5%, 10%, 15% and 20% respectively. Dried African Locust bean seeds (Parkia biglobosa) were obtained from the Crops Research Institute of the Council for Scientific and Industrial Research, Kumasi, Ghana. They were cooked overnight to soften the testa, which was carefully removed by pressing between palms and separated by swirling in water bath through a colander of 25mm sieve diameter. The resultant beans were sun dried, milled into four for incorporation into the sausage formulations. Protein, fibre and cooking yield increased significantly (P<0.05) with increasing use of WUALBF while moisture, ash, fat and cooking loss reduced significantly (P>0.05). Sensory evaluation revealed very high score (P<0.05) for formulations with 5% WUALBF for taste, favor, mouth-feel and Overall Acceptability (OA). The use of WUALBF had no significant effect (P>0.05) on appearance, tenderness, juiciness and pH of the product. Production cost reduced by 6.5%, 12.92%, 24.32% and 29.60% respectively when using 5%, 10%, 15% and 20% WUALBF in Frankfurter-type sausages. The results suggest that WUALBF has promising potential as a non-conventional extender in Frankfurter-type Sausage.